An Analysis of Morphemes on Maher Zain's Song ("One") Album - Ibrahim, Linda Fitri; Rahayu, Ona Ayu (Malewa: Journal of Multidisciplinary Educational Research, 2023)
Morphology is a branch of linguistics which studied about the intricacies of word forms and their changes. Besides that morphology also investigates the possibility of word changes that arise as a result of changes in word form. In morphology, a morpheme is the smallest grammatical unit that has meaning. In the discussion of morphemes, there are several types of morphemes namely; free morpheme, bound morpheme, inflectional morpheme and derivational morpheme. The purposes of this research are; (1) to find the types of morphemes in Maher Zain’s song and; (2) to find the dominant type of morpheme in Maher Zain’s song. The research method was qualitative method with library research design, while the source of data in this research was the lyrics of Maher Zain’s song. The data analysis in this research used Miles and Hubberman’s model. The result of this research were; (1) there were four types of morphemes on Maher Zain’s song consisted of fifteen songs in ”One” album. For free morpheme was 962 words, bound morpheme was 186 words, inflectional morpheme was 995 words and derivational morpheme was 391 words; and (2) the dominant type of morpheme on Maher Zain’s song was inflectional morpheme about 995 words.